Synthesis of Arginase Inhibitors: An Overview - Maria Cristina Molaro; Chiara Battisegola; Marica Erminia Schiano; Mariacristina Failla; Maria Grazia Rimoli; Loretta Lazzarato; Konstantin Chegaev; Federica Sodano (Pharmaceutics)
Arginase (ARG) is a binuclear manganese-containing metalloenzyme that can convert L-arginine to L-ornithine and urea and plays a key role in the urea cycle. It also mediates different cellular functions and processes such as proliferation, senescence, apoptosis, autophagy, and inflammatory responses in various cell types. In mammals, there are two isoenzymes, ARG-1 and ARG-2; they are functionally similar, but their coding genes, tissue distribution, subcellular localization, and molecular regulation are distinct. In recent decades, the abnormal expression of ARG-1 or ARG-2 has been reported to be increasingly linked to a variety of diseases, including cardiovascular disease, inflammatory bowel disease, Alzheimer’s disease, and cancer. Therefore, considering the current relevance of this topic and the need to address the growing demand for new and more potent ARG inhibitors in the context of various diseases, this review was conceived. We will provide an overview of all classes of ARG inhibitors developed so far including compounds of synthetic, natural, and semisynthetic origin. For the first time, the synthesis protocol and optimized reaction conditions of each molecule, including those reported in patent applications, will be described. For each molecule, its inhibitory activity in terms of IC50 towards ARG-1 and ARG-2 will be reported specifying the type of assay conducted.